Clinical, epidemiological and obstetrical aspects of maternal near miss in a reference maternity hospital in Northeast Brazil (Research, Society and Development, 2022)
Maternal near miss can be defined as a woman who almost died, but survived a complication that occurred during pregnancy, delivery, or puerperium, by assistance provided or by chance. The objective of this analytical, documental, and quantitative study was to evaluate the clinical epidemiological and obstetric profile of maternal near miss of patients admitted from May to December 2019 in intensive care beds of a reference maternity hospital in north-eastern Brazil who presented at least one of the diagnostic criteria. Statistical Package for Social Sciences version 25 software was used for statistical analysis. The total number of cases was 77; of these, 36 were associated with eclampsia. The predominant age group was 20 to 25 years; 41.6% were single; 63.6% had completed high school; 85.7% underwent a cesarean section; 81.8% were hospitalized during the puerperium; and 68.8% had no preexisting diseases/associated obstetric conditions. Prior placenta and hypertensive disease were more associated with the cases. Uncontrolled seizure was the most frequent clinical criterion; acute thrombocytopenia, the laboratory one; and hysterectomy, the management one. Thus, it becomes necessary to perform frequent analyses on the obstetric population assisted in a health system and its trajectory in search of care, aiming to assess the quality of care provided, since eclampsia and bleeding complications were the most frequent occurrences among the cases of and these are preventable conditions, with detection of risk factors still in the prenatal period.